2017
DOI: 10.1103/physreva.96.032702
|View full text |Cite
|
Sign up to set email alerts
|

Long-range interactions of hydrogen atoms in excited states. III. nS1S interactions for n3

Abstract: The long-range interaction of excited neutral atoms has a number of interesting and surprising properties, such as the prevalence of long-range, oscillatory tails, and the emergence of numerically large van der Waals C6 coefficients. Furthermore, the energetically quasi-degenerate nP states require special attention and lead to mathematical subtleties. Here, we analyze the interaction of excited hydrogen atoms in nS states (3 ≤ n ≤ 12) with ground-state hydrogen atoms, and find that the C6 coefficients roughly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The M 6 coefficient becomes smaller with the principal quantum number is being increased as recently observed in Ref. [17]. However, the D 6 coefficients increase as the fourth power of the principal quantum number of the excited reference states.…”
Section: Peculiarities Of Van Der Waals Coefficients For S Statessupporting
confidence: 68%
“…The M 6 coefficient becomes smaller with the principal quantum number is being increased as recently observed in Ref. [17]. However, the D 6 coefficients increase as the fourth power of the principal quantum number of the excited reference states.…”
Section: Peculiarities Of Van Der Waals Coefficients For S Statessupporting
confidence: 68%
“…The very-long-range, oscillatory tail of the van der Waals interaction is relevant only for very large interatomic distances. This conclusion holds for nD-1S interactions as well as nS-1S systems [19,23]. The reason for the suppression is that the numerical coefficients which multiply the parametric estimates given in Eq.…”
mentioning
confidence: 79%
“…However, this consideration does not take into account the scaling of the terms with the principal quantum number n. While we find that the D 6 coefficients typically grow as n 4 for a given manifold of states (see also Ref. [23]), the energy differences E m,A for adjacent lower-lying states are proportional to 1/(n − 1) 2 − 1/n 2 ∼ 1/n 3 for large n, and the fourth power of the energy difference E m,A enters the prefactor of the 1/R 2 pole term. Hence, it is interesting to compare the parametric estimates to a concrete calculation for excited nD states; this is also important in order to gauge the importance of the nonresonant contributions to the interaction energy which were left out in Ref.…”
mentioning
confidence: 86%
“…The atomic states can be classified according to the quantum number F z ; the z component of the total angular momentum commutes [11] with the total Hamiltonian given in Equation (3). Within the 6P 1/2 -6P 3/2 -1S 1/2 system, the states in the manifold F z = 3 are given as follows,…”
Section: States With F Z =mentioning
confidence: 99%
“…This is mainly due to energetic degeneracies connected with the "exchange" of the states among the two atoms. For nS-1S interactions (atomic hydrogen), this problem has recently been investigated in [3]. It was found that the interesting oscillatory 1/R 2 long-range tails [4][5][6][7][8][9][10] are numerically suppressed and become dominant only for excessively large interatomic distances, in a region where the absolute magnitude of the interaction terms is numerically insignificant.…”
Section: Introductionmentioning
confidence: 99%